2012
DOI: 10.1007/s00299-012-1256-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcriptomic analysis of the extremely boron tolerant plant Puccinellia distans with the moderately boron tolerant Gypsophila arrostil

Abstract: The molecular basis of boron tolerance of two plant species (Puccinellia distans and Gypsophila arrostil) that differ greatly in their boron tolerance was studied in this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…It has been also reported that transcript levels of a homologous gene to BOR (Bot1) is induced by high-B treatment in shoots of Puccinellia distans, an extremely high-B tolerant plant species (Padmanabhan et al 2012). High-B induction of BOR4 mRNA in A. thaliana is consistent with the physiological function of endogenous BOR4 against B were first grown in the solid media containing 0.03 mM boric acid for 7 d, and were transferred to the media supplied with 0.03 or 3 mM boric acid.…”
Section: Discussionmentioning
confidence: 98%
“…It has been also reported that transcript levels of a homologous gene to BOR (Bot1) is induced by high-B treatment in shoots of Puccinellia distans, an extremely high-B tolerant plant species (Padmanabhan et al 2012). High-B induction of BOR4 mRNA in A. thaliana is consistent with the physiological function of endogenous BOR4 against B were first grown in the solid media containing 0.03 mM boric acid for 7 d, and were transferred to the media supplied with 0.03 or 3 mM boric acid.…”
Section: Discussionmentioning
confidence: 98%
“…Described mechanisms that could be driving this are: (a) compartmentation of boron in vacuoles [49], (b) active efflux of boron from the intracellular phase into the apoplast [50], and (c) effective antioxidant responses [21,51]. In an initial step to identify and characterize internal tolerance mechanisms, we found two ESTs for an ascorbate peroxidase and a chaperone ClpB1-like in P. frigida that are up-regulated under boron stress in P. distans [41] (Supplemental Fig. S2).…”
Section: Possible Mechanisms Of the Extreme Boron Tolerance In P Frimentioning
confidence: 96%
“…Since it has yet to be sequenced, we performed the in silico DNA analysis using sequences described in Puccinellia distans, a highly boron tolerant plant, and very closely-related to P. frigida [41]. We selected four expressed sequence tags (ESTs) that were described as up-regulated in response to boron toxicity in P. distans [41]: a boron transporter (Bot1), an ABC-type transporter from the C-family, an ascorbate peroxidase, and a chaperone ClpB1-like. In addition, we also examined the expression of the Bot1 boron transporter in shoots and roots from P. frigida.…”
Section: Dna and Expression Analysesmentioning
confidence: 99%
“…Previous studies have focused on its distribution (Rechinger, 1970) and response to salt stress (Bandani and Abdolzadeh, 2007). There are little information about their physiological and biochemical mechanisms in metal stress condition (Padmanabhan et al, 2012). Due to its fast growth, large biomass, salt tolerance, and universal adaptability, it is distributed worldwide, including the extremely harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its fast growth, large biomass, salt tolerance, and universal adaptability, it is distributed worldwide, including the extremely harsh environments. Therefore, it may be useful species in environmental remediation of heavy metals contamination (Stiles et al, 2010;Padmanabhan et al, 2012). However, there are little research on its responses and tolerance to heavy metals stress.…”
Section: Introductionmentioning
confidence: 99%